Ciąża ektopowa - czynniki ryzyka, diagnostyka i leczenie = Ectopic pregnancy - risk factors, diagnostics and treatment - Magdalena Sowa; Wojciech Smuczyński; Lilla Senterkiewicz; Krystyna Kowalska; Katarzyna Ciechanowska; Iwona Głowacka (Kazimierz Wielki University, 2015)
Sowa Magdalena, Smuczyński Wojciech, Senterkiewicz Lilla, Kowalska Krystyna, Ciechanowska Katarzyna, Głowacka Iwona. Ciąża ektopowa - czynniki ryzyka, diagnostyka i leczenie = Ectopic pregnancy - risk factors, diagnostics and treatment. Journal of Education, Health and Sport. 2015;5(11):311-320. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34067 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A311-320 https://pbn.nauka.gov.pl/works/670783 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 20.11.2015.   Ciąża ektopowa - czynniki ryzyka, diagnostyka i leczenie Ectopic pregnancy - risk factors, diagnostics and treatment   Magdalena Sowa1, Wojciech Smuczyński1, Lilla Senterkiewicz2, Krystyna Kowalska3, Katarzyna Ciechanowska1, Iwona Głowacka4   1Katedra i Zakład Laseroterapii i Fizjoterapii, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. L. Rydygiera w Bydgoszczy 2Katedra i Zakład Diagnostyki Laboratoryjnej, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. L. Rydygiera w Bydgoszczy 3Zakład Neurotraumatologii, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. L. Rydygiera w Bydgoszczy 4Katedra i Klinika Rehabilitacji, Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum im. L. Rydygiera w Bydgoszczy     Adres do korespondencji/ Address for correspondence: Magdalena Sowa Katedra i Zakład Laseroterapii i Fizjoterapii Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy ul. Techników 3 85 - 801 Bydgoszcz           Streszczenie   Wprowadzenie: Ciąża ektopowa stanowi poważny problem kliniczny, w którym dochodzi do zagnieżdżenia komórki jajowej poza jamą macicy. Częstość jej występowania w ostatnich latach wykazuje tendencję wzrostową. Każde ektopowe zagnieżdżenie jaja płodowego stanowi stan zagrożenia życia dla kobiety ciężarnej. Mimo, iż znane są czynniki ryzyka nieprawidłowej implantacji blastocysty, nie ma skutecznych sposobów zapobiegania ciążom pozamacicznym. Cel pracy: Celem pracy była analiza czynników ryzyka, diagnostyki oraz współczesnych metod leczenia ciąży ekotopowej. Metodyka: W celu przedstawienia problemu posłużono się metodą analizy piśmiennictwa dostępnego w internetowych, medycznych bazach danych. Podsumowanie: Na przełomie ostatnich lat nastąpił rozwój zaawansowanych metod diagnostycznych, co przyczyniło się do wcześniejszego wykrywania patologii oraz umożliwiło wdrożenie odpowiedniego leczenia, dostosowanego do możliwości terapeutycznych zakładu opieki zdrowotnej oraz dalszych planów rozrodczych pacjentki. Obecnie trwają prace nad poznaniem czynników genetycznych, sprzyjających ektopii jaja płodowego.   Słowa kluczowe: ciąża ektopowa, diagnostyka, leczenie.         Summary   Ectopic pregnancy - risk factors, diagnostics and treatment Introduction: Ectopic pregnancy is a serious clinical problem, in which the egg cell is implanted outside the uterine cavity. Its incidence has been increasing in the last years. Each ectopic implantation of the ovum constitutes life-threatening condition for a pregnant woman. Although the risk factors of improper blastocyst implantation are known, there are no effective methods for preventing ectopic pregnancies. Objective: Aim of this study was to analyze the risk factors, diagnostics and contemporary methods of ectopic pregnancy treatment. Methodology: In order to present the problem, the analysis method of literature available in online, medical databases has been used. Summation: Within the last few years, the development of advanced diagnostic methods has occurred, which contributed to the earlier detection of pathology and enabled the implementation of appropriate treatment, adapted to the therapeutic possibilities of the healthcare facility and further reproductive plans of the patient. The works are currently in progress to recognize the genetic factors that conduce to ectopia of the ovum.   Key words: ectopic pregnancy, diagnostics, treatment.